PENERAPAN SIRKULAR EKONOMI BAGI SISWA MELALUI PELATIHAN PEMBUATAN HAND SANITIZER DARI ECO-ENZYME - Firmansyah, Arief; Mu’tamar, M Fuad Fauzul; Probowati, Banun Diyah; Lisdayana, Nurmalisa; Nurhidayah, Enung Siti; Sugiharto, Sugiharto; Asfan, Dian Farida; Fansuri, Hamzah; Rakhmawati, Rakhmawati; Hidayat, Khoirul (Departemen Teknologi Pertanian Universitas Hasanuddin, 2023)
This decade is developed a maximal utilization of products until there are no leftovers, known as the circular economy. The concept explained that organics waste should be used to produce a good product like eco-enzyme. Eco-enzyme is a fermentation product that has a lot of benefits for agriculture till personal sanitation. The benefit of circular economy through eco-enzyme application must be promoted and disseminated. The workshop that targeted teenagers provided long-term effects for applying the circular economy concept. The empowerment event aims to disseminate the circular economy concept through hand-sanitizer production from eco-enzyme, which is taken from organic waste. The object of this event was students in 10th and 11th grade from Muhammdiyah 2 High School, Surabaya. The workshop used a combination of methods between lecturing and demonstration. This workshop was assessed by 5 indicators, i.e., workshop theme, competencies of lecturer, communication effectiveness, workshop duration, and availability of visual aid. Data was collected by the questioner at the end of the workshop. The result showed that 4 of 5 indicators provided good responses. Indicators of workshop duration need to evaluate for the next event. The workshop succeeded in providing knowledge about how to make hand sanitizer from eco-enzyme. The next event should discuss and demonstrate the production of another personal hygiene.